Determining Stability in Posterior Wall Acetabular Fractures. Issue 10 (October 2015) - Firoozabadi, Reza; Spitler, Clay; Schlepp, Calvin; Hamilton, Benjamin; Agel, Julie; Routt, Milton "Chip"; Tornetta, Paul
Abstract : Objectives: To determine if the radiographic parameters of femoral head coverage by the intact posterior wall, acetabular version, and location of the fracture or a history of dislocation were determinates of hip stability in patients with posterior wall acetabular fractures. Design: Retrospective review. Setting: Level I trauma hospital. Patients: One hundred eighty-five consecutive patients with isolated unilateral posterior wall (OTA 62-A1) acetabular fractures. Intervention: Patients underwent dynamic stress fluoroscopic examination under general anesthesia to determine hip stability. Main Outcome Measurements: A number of radiographic measurements were performed, and an examination under anesthesia served as a standard to compare stable versus unstable hips. Results: Examination under anesthesia (EUA) determined 116 hips to be stable and 22 hips as unstable. Moed and Keith method of wall size measurements and cranial exit point of fracture was statistically different between stable and unstable hips. Twenty-three percent of the unstable hips had wall sizes less than 20%. Average cranial exit point of fracture from dome was 5.0 mm in the unstable group and 9.5 mm in the stable group, and fractures that extend into the dome demonstrate a statistically significant increase in hip instability. Conclusions: Determination of hip stability can be challenging in patients with posterior wall acetabular fractures. Our data suggest that the location of the exit point of the fracture in relation to the dome of the acetabulum is a radiographic marker that can be used to aid physician in determining stability, and wall sizes less than 20% is not a reliable indicator of stability. Level of Evidence: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.